Cadet Recruitment Analysis of Naval Academy in Utilizing Demographic Bonuses by Using The SWOT Methods - Siswanto Siswanto; Achmad Toripin (JURNAL EKBIS, 2022)
The purpose of this research is to know a clear picture of the organizational structure of Brigif-4 Mar / BS in implementing Binpotmar. Knowing a clear picture of the human resources (HR) of coastal communities in Pulau Pahawang Village and Pulau Tegal Village. Knowing a clear picture of Brigif-4 Mar / BS with other stakeholders in Binpotmar activities. This research uses qualitative research methods with descriptive surveys, and in processing data using NVivo 12 Plus and analyzed using the Triangulation method. The results showed that the Intelligence Staff who was in charge of the Maritime Potential Development activities Brigif-4 Mar / BS was in principle able to carry out their duties well but not optimally. Binpotmar Brigif-4 Mar / BS which was held in Pahawang Island Village and Tegal Island could not run optimally. Coordination and cooperation between Brigif-4 Mar / BS in the implementation of Binpormar with other stakeholders has been going well but only ceremonial in nature.